-12-7x=-103

Simple and best practice solution for -12-7x=-103 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -12-7x=-103 equation:


Simplifying
-12 + -7x = -103

Solving
-12 + -7x = -103

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '12' to each side of the equation.
-12 + 12 + -7x = -103 + 12

Combine like terms: -12 + 12 = 0
0 + -7x = -103 + 12
-7x = -103 + 12

Combine like terms: -103 + 12 = -91
-7x = -91

Divide each side by '-7'.
x = 13

Simplifying
x = 13

See similar equations:

| 0.2n=6 | | 4b+6=32 | | a(8d-5)+13=12d-2 | | 198X=2376 | | G+26=324 | | 9=13+x | | 4n=56 | | n=(.25)(3.5) | | -3(w+4)=3w-8+2(5w+2) | | 7+5b=27 | | -4(-6w+4)-3w=5(w-4)-6 | | 8x+11=27 | | -4-(1)= | | 5(u+3)=-3(5u-9)+5u | | 63=3ab+3 | | t+8=-3 | | 2+4n=n+10 | | x+9/2=23/5-x-3/5 | | 65-40= | | 65(40)= | | 6x-16=43 | | 55-35= | | x-35=20 | | (8x+3)+6=2 | | 5(2x+8)-5x=(5x+6) | | 65/40= | | 6p - 5 = 2p + 7 | | 6p-5=2p+ 7 | | 6w/3=-4 | | 27x+1324=1999 | | -10/2= | | 6x-8=-2x |

Equations solver categories